The Influence of Educational Promotion and Brand Image on Students Decision to Choose Madrasah - Leuwol, Ferdinand Salomo; Kartiko, Ari; Nasar, Ismail; Idrus, Imriani; Putra, Freddrick Tiagita (Universitas Muhammadiyah Ponorogo, 2023)
Promotion is all efforts made by educational institutions to introduce services to prospective new students, persuade/provide information so that consumers are interested. Besides that, brand image also greatly influences the number of prospective new students in educational institutions. A positive brand image is a very valuable asset and a strong capital to influence prospective new students. The existence of promotional activities and a good brand image will influence the students' decision to choose the educational institution. This study uses a quantitative research method with a causality approach. The sample in this study were 84 respondents using a proportionate random sampling technique, namely where all members have the same opportunity to be sampled according to their proportions. Data collection was carried out by distributing questionnaires to respondents and tested using multiple linear regression tests with the help of SPSS 22. The results showed that the promotion variable (X1) had a positive and significant effect on the decision to choose (Y1), seen from testing the hypothesis T test where tcount > t table (2.635> 1.989) and a significant level of less than 0.05 (0.010 <0.05), brand image variable (X2) has a positive and significant influence on the decision to choose (Y1), seen from testing the hypothesis t test where tcount > ttable (4.449> 1.989) and a significance value of less than 0.05 (0.000 <0.05), the promotion variable (X1) and brand image (X2) on the decision to choose (Y1) have a simultaneous effect, seen from the F test, namely Fcount > Ftable (26.601 > 3.11) and a significance level of less than 0.05 (0.000 > 0.05).